The Type of Taboo Words Used by The Characters in Bad Boys for Life Movie - Antari, Lily; Santika, I Dewa Ayu Devi Maharani (Journal of Language and Applied Linguistics, 2025)
The use of taboo words is prohibited in some places or situations. But even the use of taboo words are prohibited, a lot of people still use them, especially for teenagers. They use taboo words to express their emotion. Taboo words are commonly used in movies or filmswith comedy genres. The aim of this research is focused on analyzing the type of taboo word that is used by the character in the Bad Boys for Life movie. The researcher used this film as the data source because it consists of a lot of taboo words used by the characters because this film has comedy and action genres. The researcher used observation method in collecting the data by watches and observes the movie than taking note the important words. This research used the theory proposed byBatistella (2005)to analyze the data. According to Batistella (2005), there are 4 types of taboo words: Profanity, Epithet, Vulgarity, and Obscenity. The result of this research is the highest frequency type of taboo word found is Vulgarity with 12 words, and the second is Epithet with 4 words and the lowest frequency is Profanity and Obscenity with 3 words each type.